(untitled) (Research, Society and Development, 2020)
Arterial hypertension, consists of a pathology where there is an increase in the physiological levels of blood pressure, there is a therapeutic arsenal available for the treatment of hypertension. this pathology, they present indisputable efficacy, few adverse effects and low toxicity, however they are targets of drug interactions with drugs that present the same site of hepatic microsomal metabolism, which can decrease their therapeutic efficacy. The aim of this research was to analyze the drug interactions of angiotensin II receptor antagonists (ARA II). It is characterized as a documentary research, with a quantitative, retrospective, analytical-discussion approach that uses the Micromedex Solutions® database, to obtain drug interactions. The results show that the drugs that are substrates for the CYP pathway, especially the CYP3A4 and CYP2C9 isoforms are more likely to interact, the drug losartan with the highest number of interactions in this study, presents metabolism with the CYP3A4 and CYP2C9 isoforms, the drugs that have alternative metabolism pathways, tend to have as little interaction as possible. In view of this, ARA II is currently one of the best classes for its treatment, however the use of this class of drugs requires observation by the prescribers and accompanying pharmacists.